2009
DOI: 10.1177/1350507608099313
|View full text |Cite
|
Sign up to set email alerts
|

Three Moves for Engaging Students in Critical Management Studies

Abstract: The intellectual and substantive resources of Critical Management Studies are difficult to use in the typical managerialist undergraduate classroom. Their emphasis on power, exploitation and subordination often `jar' with conventional curricula. In this article I offer a `three moves' approach to teaching critical management studies that provides a means of `smoothing' the `entry' of these resources into undergraduate teaching. The `three moves' involve (1) distinguishing between different forms of knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…One of the concerns of contemporary pedagogy in business schools is that undergraduates are at risk of retaining or absorbing an uncritical perspective on management and organizations (Prichard, 2009). Unless otherwise prompted or encouraged to become 'critical beings' (Dehler, 2009, passim), students may not question a number of tacit managerialist norms and assumptions.…”
Section: Business Schools and Pedagogymentioning
confidence: 99%
“…One of the concerns of contemporary pedagogy in business schools is that undergraduates are at risk of retaining or absorbing an uncritical perspective on management and organizations (Prichard, 2009). Unless otherwise prompted or encouraged to become 'critical beings' (Dehler, 2009, passim), students may not question a number of tacit managerialist norms and assumptions.…”
Section: Business Schools and Pedagogymentioning
confidence: 99%
“…Otro problema es que las estructuras de gobierno de las universidades británicas han sido muy proclives a aplicar los principios elementales del gerencialismo a la gestión universitaria, especialmente en algunos centros: paradigmático es el caso de Warwick, convertida en ejemplo extremo de "universidad emprendedora" bajo la gestión del controvertido geógrafo Nigel Thrift, cuyo autoritarismo y gestión basada en la presión por resultados ha terminado precipitando la salida de muchos académicos críticos (Parker, 2014). Finalmente, un reto adicional es el de un alumnado no necesariamente atraído por la aventura del saber, pragmático y obsesionado con la inserción laboral (y en el caso británico norteamericano, posiblemente endeudado), con poca motivación hacia los estudios críticos, y que requieren estrategias docentes concretas (Prichard, 2009). ¿Podríamos hablar, por tanto, de crisis de los Critical Management Studies?…”
Section: Crisis Financiera Reajuste Neoliberal Y Critical Managementunclassified
“…For example, one trial team could attempt to prove that Expectancy Theory is effective because motivation is an objective, measurable phenomenon while the other side contends that a nominal, subjectivist approach better describes the reasons why people act as they do. The use of dramatic scripts based on case studies or actual organizational practices has been found to effectively introduce undergraduates to critical management education (Prichard, 2009).…”
Section: Mock Trials In Other Disciplinesmentioning
confidence: 99%